A Stairway to Heaven: Daoist Self-Cultivation in Early Modern China - Enckevort, Paul van (Asian Studies E-Books Online, Collection 2025., 2025)
By the eleventh century, communities of religious practitioners in China had developed a theory and practice of meditative self-cultivation that combined the so-called Three Teachings. By the seventeenth century, Wu Shouyang created a synthesis of the various lineages of this "inner alchemy," combining it with elements from Buddhism and Confucianism. By the late nineteenth century, his writings had become bestsellers in the genre and his became the standard account of this tradition. This first book-length English-language study of Wu Shouyang's life and works introduces his remarkable life and formulates answers to fundamental questions about this important tradition.